Ekplorasi Peran Dukungan Teman Sebaya dalam Membangun Kepercayaan Diri dan Kontribusi Mahasiswa Aktif Pendidikan Sosiologi FKIP Untirta - afsari, husniya; Afrizal, Stevany (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
The self-confidence that arises in students from the support of their peers greatly influences their mental and emotional stability. Students who are confident tend to be able to actively participate in class and campus activities. By participating in these activities, students can enhance their academic and non-academic learning experiences. This study aims to identify how peer support can build student selfconfidence on campus, as well as analyze this self-confidence in student involvement in academic and non-academic activities. Using a descriptive qualitative approach with narrative analysis techniques through four stages: identifying narrative structures, exploring the meaning behind coding narratives accompanied by analysis for recurring themes, mapping story patterns, and reflection and interpretation to reflect students’ collective experiences. The results of this study indicate that peer support in building self-confidence, active contributions in campus activities and academic success plays a significant role both in active students of sociology education, FKIP Untirta, during their studies and in the long term for their future. Keyword: peers, students, self-confidence, active contribution